1995
DOI: 10.1007/bf00037025
|View full text |Cite
|
Sign up to set email alerts
|

The maize transposable element Ac is mobile in the legume Lotus japonicus

Abstract: To evaluate the prospects for transposon mutagenesis in the autogamous diploid legume Lotus japonicus, the behaviour of the maize transposable element Ac was analysed in the progeny of 38 independent transgenic plants. The conditions for monitoring donor site excision using histochemical localization of beta-glucuronidase activity or the alternative spectinomycin resistance assay were established, and used to follow Ac mobility through two generations. Somatic excision was monitored as variegated cotyledons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 37 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…Eight monogenic recessive mutant alleles defined below as nap1 -1, nap1-2, and nap1-3, and pir1-1, pir1-2, pir1-3, pir1-4, and pir1-5 (Table 1), corresponding to two lotus loci, Nap1 and Pir1, respectively, were found in three independent screens for symbiotic mutants. nap1-1 and pir1-1 were isolated from a mutant population that was originally established to identify transposon-tagged mutants (Thykjaer et al, 1995;Schauser et al, 1998), while the remaining alleles were found in two independent ethyl methanesulfonate (EMS) populations (Murray et al, 2006;Yano et al, 2006). nap1 and pir1 mutants were identified as small nitrogenstarved plants when grown on nitrogen-deficient nutrient medium.…”
Section: Nodulation Phenotype Of Nap1 and Pir1 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight monogenic recessive mutant alleles defined below as nap1 -1, nap1-2, and nap1-3, and pir1-1, pir1-2, pir1-3, pir1-4, and pir1-5 (Table 1), corresponding to two lotus loci, Nap1 and Pir1, respectively, were found in three independent screens for symbiotic mutants. nap1-1 and pir1-1 were isolated from a mutant population that was originally established to identify transposon-tagged mutants (Thykjaer et al, 1995;Schauser et al, 1998), while the remaining alleles were found in two independent ethyl methanesulfonate (EMS) populations (Murray et al, 2006;Yano et al, 2006). nap1 and pir1 mutants were identified as small nitrogenstarved plants when grown on nitrogen-deficient nutrient medium.…”
Section: Nodulation Phenotype Of Nap1 and Pir1 Mutantsmentioning
confidence: 99%
“…nap1-1 previously called sym67 was found in a population screened for Ac-tagged mutants (Thykjaer et al, 1995;Sandal et al, 2006), nap1-2 and nap1-3 mutants previously called S12-5A and S90-D originate from an EMS-mutagenized population (Murray et al, 2006). pir1-1 previously called sym40 was found in a population screened for Ac-tagged mutants (Thykjaer et al, 1995;Sandal et al, 2006), pir1-2, pir1-3, pir1-4, and pir1-5 originate from EMS populations and were previously called sym80 (Kawaguchi et al, 2002), S14-3, S57-F, and B31-C (Murray et al, 2006), respectively. Seeds of the wild type, nap1-1, pir1-1, and nap1-1pir1-1 double mutant were surface sterilized as described previously (Handberg and Stougaard, 1992) and grown for 6 weeks in Magenta boxes or 5 weeks on solid quarter-strength B&D (Broughton and Dilworth, 1971) slants with 1 mM KNO 3 .…”
Section: Plant Materialsmentioning
confidence: 99%
“…For both systems, mutant plants affected in diffbrent steps of nodule development have been identified (Webb et al, 1994;Benaben et al, 1995;Sagan et al, 1995). Transposon mutagenesis is also feasible (Thykjaer et al, 1995). We await exciting developments in the molecular genetics of these model systems over the next few years.…”
Section: Genetic Analysis Of Nodule Developmentmentioning
confidence: 99%
“…Both pathways are active in alfalfa and sainfoin (Koupai et al 1993a,b), whereas only the 2R3R4S pathway has been found in Arabidopsis (Xie et al 2003). (')-Catechin has been shown to have anti-bacterial activity in some nonLotus species (Bais et al 2002;Veluri et al 2004). CONCLUSION Phytochemical profiling has provided evidence of the stimulation of flavanols, phenolic acids, flavan-3-ols, and PAs in leaves L. angustissimus leaves and the tan mutants and in L. c. var.…”
Section: L M)mentioning
confidence: 99%
“…Developmental mutants, nodulation mutants, and tan mutants accumulating leaf PA have also been recovered from Gifu B129 Tn/T-DNA-tagged populations (Thykjaer et al 1995;Gruber et al 1998;Schauser et al 1998;Martirani et al 1999;Webb et al 2000;Ooki et al 2005).…”
mentioning
confidence: 99%